Estimates of survival and population development of the Osprey Pandion haliaetus, Common Buzzard Buteo buteo, and Sparrowhawk Accipiter nisus in Sweden - Ryttman, Hans (Ornis Svecica, 1994)
I have used ring recoveries to estimate survival rate and population trends for the Osprey, Common Buzzard and Sparrowhawk in Sweden. About 65% of the Ospreys survive their first year and about 81% the years thereafter. The same estimates for the Common Buzzard are 48% in the first year and 76% in the other years and for the Sparrowhawk 36% in the first year and 64% in the other years. With these figures the Osprey and the Sparrowhawk ought to increase their breeding populations in Sweden. However, the population of the Osprey is not at all or very slowly increasing, perhaps depending on shortage of breeding sites in natural trees and/or a higher first breeding age than assumed. The population trend in the Sparrowhawk depends mostly on cold winters and the population fluctuates accordingly. The Common Buzzard population seem to decline because of bad breeding results.